Antioxidant Techniques And Oxidative Stress In Dermatology (International Journal of Food and Nutritional Sciences, 2022)
A prooxidant-antioxidant imbalance causes oxidative stress, which damages cells. Free radicals that are produced during normal aerobic metabolism and pathological inflammatory processes, such as reactive oxygen or nitrogen species, mediate it. Skin acts as a defence mechanism that is crucial in preventing both internal and external noxious stimuli and preserving homeostasis. It is becoming more and more clear that oxidative stress plays a role in a variety of skin problems, and that antioxidative tactics can be used as quick and simple ways to treat these conditions. Here, we examine the therapeutic use of antioxidants in dermatology and the dysregulation of antioxidant systems.